Current mode fuzzy based controller for multilevel inverter - Misiran, Mohamad Anim (2013)
The thesis presents the control design for H-bridge cascaded multilevel inverter using current mode fuzzy based controller. The cascaded multilevel inverter synthesizes a five level output voltage from a several independent source. Using multilevel technique, the amplitude of the voltage is increase, stress in the switching device is reduce and the overall harmonics profile is improve. Fuzzy logic is utilized to compensate any changes at the output due to disturbance, system parameters changes, nonlinearities and etc. The full inverter system, is designed and simulated using Matlab-Simulink. From the simulation results, it was shown that the controller is capable to compensate disturbances hence verify the design.